Hydrogen bonds are a primary driving force for de novo protein folding. Issue 12 (4th December 2017) - Lee, Schuyler; Wang, Chao; Liu, Haolin; Xiong, Jian; Jiji, Renee; Hong, Xia; Yan, Xiaoxue; Chen, Zhangguo; Hammel, Michal; Wang, Yang; Dai, Shaodong; Wang, Jing; et al.
Abstract : The yield of protein refolding is reciprocal to the number of proline residues in the target protein. Hydrogen bonds are the primary driving force for de novo protein folding Abstract : The protein‐folding mechanism remains a major puzzle in life science. Purified soluble activation‐induced cytidine deaminase (AID) is one of the most difficult proteins to obtain. Starting from inclusion bodies containing a C‐terminally truncated version of AID (residues 1–153; AID 153 ), an optimized in vitro folding procedure was derived to obtain large amounts of AID 153, which led to crystals with good quality and to final structural determination. Interestingly, it was found that the final refolding yield of the protein is proline residue‐dependent. The difference in the distribution of cis and trans configurations of proline residues in the protein after complete denaturation is a major determining factor of the final yield. A point mutation of one of four proline residues to an asparagine led to a near‐doubling of the yield of refolded protein after complete denaturation. It was concluded that the driving force behind protein folding could not overcome the cis ‐to‐ trans proline isomerization, or vice versa, during the protein‐folding process. Furthermore, it was found that successful refolding of proteins optimally occurs at high pH values, which may mimic protein folding in vivo . It was found that high pH values could induce the polarization of peptide bonds, which may trigger the formation of protein secondary structures through hydrogen bonds. It is proposed that a hydrophobic environment coupled with negative charges is essential for protein folding. Combined with our earlier discoveries on protein‐unfolding mechanisms, it is proposed that hydrogen bonds are a primary driving force for de novo protein folding.